Kemampuan pemecahan masalah matematis siswa ditinjau dari self-confidence siswa pada materi bangun ruang sisi datar - Randi Junaedi Saputra; Deddy Sofyan; Dian Mardiani (Institut Pendidikan Indonesia, 2023)
Abstract One of the factors of failure in learning is the lack of students' mathematical problem-solving abilities. One of the factors that affect the ability to solve mathematical problems is self-confidence. The purpose of this study is to analyze mathematical problem-solving ability based on high self-confidence. This study uses a qualitative method, the population in this study is public junior high school students in the Malangbong sub-district. The sample was chosen by 4 students to be the subject of the interview. The instruments used are questionnaires, tests, and interview guidelines. The results obtained from this study, some students are not able to understand the problem of rectangular pyramids, most students are not able to understand the problem of rectangular blocks and pyramids, all students are not able to plan solutions, namely the formula for the perimeter of the pyramid, the formula for the length of the entire side of the beam, the formula for the surface area rectangular pyramid, and the formula for the area of the inner wall in the form of a block, all students were not able to plan using the formula for the perimeter of the pyramid, the formula for the length of the entire side of the beam, the formula for the surface area of a rectangular pyramid, and the formula for the area of the inner wall in the form of a block. Abstrak Salah satu faktor ketidak berhasilan dalam belajar yaitu kurangnya kemampuan pemecahan masalah matematis siswa. Salah satu faktor yang mempengaruhi kemampuan pemecahan masalah matematis yaitu self-confidence. Tujuan dari penelitian ini untuk menganalisis kemampuan pemecahan masalah matematis berdasarkan self-confidence tinggi. Penelitian ini menggunakan metode kualitatif, populasi pada penelitian ini adalah siswa SMP Negeri yang berada di kecamatan malangbong. Sample dipilih 4 siswa untuk dijadikan subjek wawancara. Instrumen yang digunakan adalah angket, tes, dan pedoman wawancara. Hasil yang diperoleh dari penelitian ini, sebagian siswa tidak mampu memahami masalah limas persegi empat, sebagian besar siswa tidak mampu memahami masalah balok dan limas persegi panjang, semua siswa tidak mampu merencanakan penyelesaian yakni rumus keliling limas, rumus panjang seluruh rusuk balok, rumus luas permukaan limas persegi panjang, dan rumus luas dinding bagian dalam berbentuk balok, semua siswa tidak mampu melakukan rencana dengan menggunakan rumus keliling limas, rumus panjang seluruh rusuk balok, rumus luas permukaan limas persegi panjang, dan rumus luas dinding bagian dalam berbentuk balok.